ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHIKONTRIBUSI SEKTOR PARIWISATA UNTUK MENDUKUNG PENINGKATAN PADDI KOTA PALEMBANG - Fauziah Afriyani (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2015)
The purpose of the study was to find out and analyze how the influence the number of tourist, tourist attractions, hotel occupancy rates and revenue against to support the increase in local revenue in the city of Palembang. This study used a qualitative and quantitative analysis technique where method using econometric regression models. The result showed that the variable number of attractions, the number of tourists, and the hotel occupancy rate greatly affects local revenues in the tourism sector. the tourism sector should contribute to the PAD could be increased again by considering supporting factors such as accommodation facilities (hotels and travel cot), restaurants, travel agencies, tourism, power tourism attractions, tourism education institutions and inhibiting the consolidation of the tourism industry as a trade mark Palembang as a tourist destination and the accessibility of foreign direct flights to Palembang.